Contribution of Traditional Mehule Games to Improve Understanding of Local Wisdom Material and Students' Interest in Learning Science Subjects in Grade IV of SDN Were'a - Evayanti, Ni Wayan Wahyu; Misnah, Misnah; Ratu, Bau (Journal of Education Method and Learning Strategy, 2025)
The cultural heritage left by the ancestors and predecessors of the Indonesian nation is countless, ranging from regional languages, regional clothing, dances and other regional arts. The research problem formulation is how the traditional Mehule game contributes to improving the understanding of local wisdom material in class IV SDN Were'a. How the contribution of the conventional Mehule game in enhancing students' interest in learning in class IV SDN Were'a. Research objectives: To analyze the contribution of the traditional Mehule game in improving students' interest in learning in class IV SDN Were'a. Research Method This type of research is descriptive qualitative research using an ethnographic approach. The ethnographic approach is an approach that is carried out empirically and theoretically to produce a deeper picture and analysis of culture in society, in this case, the traditional Mehule game. Research results The TGT model was chosen because it was considered appropriate for building student cooperation, fostering a healthy competitive spirit, and improving understanding of concepts through educational games. The game used is a typical Morowali game, namely the Mehule game. Research conclusions: Students become more active, enthusiastic, and able to connect learning materials with their local cultural experiences.